The Impact of Co-opetition on the Challenges of Internationalisation for SMEs on the Chinese market - Jiang, Shuwei (My University, 2019)
The world’s economy is approaching to be integrated as a whole and the interactions between companies from different countries are closer and easier than ever. Under such a context, SMEs are evolved from local actors into international players. During the process of internationalisation, SMEs are benefited from international opportunities in developing their competitiveness and improving their overall performances. At the same time, a number of challenges are accompanied creating obstacles for SMEs in achieving their business targets. The degree of challenges is found to be increasing while the international operations spread into emerging markets like China. It is advised to overcome the challenges of internationalisation through forming cooperative alliances with other companies. Among different types of cooperation, co-opetition, a relationship consists of simultaneous cooperation and competition, receives scarce attention. Whether co-opetition could positively impact on solving the challenges of internationalisation for SMEs has not widely studied and then becomes the interest of this work. A qualitative research was conducted on four case organisations that are all SMEs from European automotive industry and involved in co-opetitive relationships on the Chinese market. A conclusion is arguably drawn to evidence that a list of benefits of co-opetition can positively solving numerous challenges that SMEs confront during their internationalisation.
Keywords: Co-opetition; Co-opetitive relationship; Internationalisation; SMEs; Automotive industry; Chinese market.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|